-5(x+2)-17=11+7

Simple and best practice solution for -5(x+2)-17=11+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x+2)-17=11+7 equation:


Simplifying
-5(x + 2) + -17 = 11 + 7

Reorder the terms:
-5(2 + x) + -17 = 11 + 7
(2 * -5 + x * -5) + -17 = 11 + 7
(-10 + -5x) + -17 = 11 + 7

Reorder the terms:
-10 + -17 + -5x = 11 + 7

Combine like terms: -10 + -17 = -27
-27 + -5x = 11 + 7

Combine like terms: 11 + 7 = 18
-27 + -5x = 18

Solving
-27 + -5x = 18

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + -5x = 18 + 27

Combine like terms: -27 + 27 = 0
0 + -5x = 18 + 27
-5x = 18 + 27

Combine like terms: 18 + 27 = 45
-5x = 45

Divide each side by '-5'.
x = -9

Simplifying
x = -9

See similar equations:

| 11x+4=12x-8 | | 10x+7y=36 | | 5/60=x/8 | | (-2+4i)-(3+9i)=0 | | 3a+19+15a+38= | | y=1/4x-4/3 | | 4x^2-16x= | | -10x-3(9-x)=4(-2x+5)-9 | | (3c-5)=(c+3) | | 6(2x+5)=102 | | 5(i+2)=2(r-4)-6 | | -11x4/7 | | 0.05x+0.20y= | | 5-a=a-5*3+1 | | -11x4z/7 | | 18x-6/3 | | -x+6=-8 | | y=13-3 | | 10x^2=134 | | 6p+20q+6= | | 0.3(n-5)=0.4-2(n-7) | | 10(7-x)=0 | | X(2y+3)+x(5y+4)= | | 0.05x+0.20y=4.20 | | 6(2x-3)/4=16-(-18) | | .1x+1.4=.3 | | 6a^2-2c+2a^2-2c^2= | | x^2+28x+21=0 | | (T+4)+(t+3)+(t-1)=39 | | -3+14=m-8 | | (1k+12)(3k-2)= | | 25a=23 |

Equations solver categories